The Transport Contract in Albanian Civil Code: A Systemic Analysis - Gjeta, Arber; Bylykbashi, Juliana (Mediterranean Journal of Social Sciences, 2020)
The transport legislation in Albania has a character of specialty. Through this paper we aim to offer an analysis of the Albanian legal provisions on transport contract according to the Civil Code. This study will deal with the contract of transport of goods. The analysis of the contract will be in a historical, empiric and doctrinal point of view on the regulation offered by the Civil Code and the similarities to the Italian Civil Code. The actual regulation of the contract of transport in Albania is relatively new and there are only a few claims brought into courts that make very difficult a deep analysis of the implementation the legislation. The lack of causes brought into courts mainly has to be recognized to the arbitration clauses in favor of foreign arbitrators as for the transport of goods by sea or the solution on transaction basis as well as, regarding Civil Code provisions, the camouflage of the contract of transport with other types of contracts.